2007
DOI: 10.1038/ng.2007.54
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary proteins link basal body polarization to planar cell polarity regulation

Abstract: Planar cell polarity (PCP) refers to coordinated polarization of cells within the plane of a cell sheet. A conserved signaling pathway is required for the establishment of PCP in epithelial tissues and for polarized cellular rearrangements known as convergent extension. During PCP signaling, core PCP proteins are sorted asymmetrically along the polarization axis; this sorting is thought to direct coordinated downstream morphogenetic changes across the entire tissue. Here, we show that a gene encoding a ciliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
341
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(371 citation statements)
references
References 49 publications
21
341
3
1
Order By: Relevance
“…This hypothesis was validated by the findings of similar stereociliary orientation defects in mouse mutants of other PCP orthologs, including Celsr1 (an ortholog of flamingo [Curtin et al 2003]), Fz3 and -6 (Wang et al 2006b) and Dvl1, -2, and -3 (Wang et al 2005;Etheridge et al 2008). Furthermore, mouse PCP proteins display asymmetric plasma membrane distribution in the organ of Corti, and mutation of one PCP gene perturbs the membrane localization of other PCP proteins (Wang et al 2005(Wang et al , 2006bMontcouquiol et al 2006;Jones et al 2008). The asymmetric membrane localization of PCP proteins is a unique feature first described in flies and is thought to provide a mechanism for PCP proteins to propagate polarity information across the entire field of epithelium (Amonlirdviman et al 2005;Wu and Mlodzik 2008).…”
Section: Stereociliary Bundle Orientationsupporting
confidence: 48%
See 1 more Smart Citation
“…This hypothesis was validated by the findings of similar stereociliary orientation defects in mouse mutants of other PCP orthologs, including Celsr1 (an ortholog of flamingo [Curtin et al 2003]), Fz3 and -6 (Wang et al 2006b) and Dvl1, -2, and -3 (Wang et al 2005;Etheridge et al 2008). Furthermore, mouse PCP proteins display asymmetric plasma membrane distribution in the organ of Corti, and mutation of one PCP gene perturbs the membrane localization of other PCP proteins (Wang et al 2005(Wang et al , 2006bMontcouquiol et al 2006;Jones et al 2008). The asymmetric membrane localization of PCP proteins is a unique feature first described in flies and is thought to provide a mechanism for PCP proteins to propagate polarity information across the entire field of epithelium (Amonlirdviman et al 2005;Wu and Mlodzik 2008).…”
Section: Stereociliary Bundle Orientationsupporting
confidence: 48%
“…The asymmetric membrane localization of PCP proteins is a unique feature first described in flies and is thought to provide a mechanism for PCP proteins to propagate polarity information across the entire field of epithelium (Amonlirdviman et al 2005;Wu and Mlodzik 2008). Lastly, the asymmetric distribution of PCP proteins is observed prior to overt morphological polarization of stereociliary bundles (Wang et al 2006a;Jones et al 2008), consistent with PCP signaling playing a role in establishing stereocilia orientation in mice.…”
Section: Stereociliary Bundle Orientationmentioning
confidence: 58%
“…16,17,29 It has been shown that primary cilia have a critical role in the development of the growth plate. Disturbance of the intraflagellar transport system leads to a depletion of cells with primary cilia and defects in the growth plate such as disruption of cell shape and lack of columnar orientation, which suggests defects in cell movement/rotation.…”
Section: Discussionmentioning
confidence: 99%
“…15 In several tissues, the organization of primary cilia has been shown to reflect cell polarity. [16][17][18] In cartilage, it has been reported that primary cilia have a specific orientation pointing away from the articular surface in articular chondrocytes or located at the center of the columnar cells in the growth plate. 3,19,20 In the extensor tendon, cilia are aligned parallel to the collagen fibers and the long axis of the tendon.…”
mentioning
confidence: 99%
“…Interestingly, there is evidence that Disheveled regulates cilia formation in Xenopus by facilitating centriole migration and basal body docking (Park et al, 2008). On the other hand, disruption of cilia function appears to influence planar cell polarity, at least in the inner ears (Ross et al, 2005;Jones et al, 2008).…”
Section: Introductionmentioning
confidence: 99%